U.N. International Covenant on Civil and Political Rights : Nowak's CCPR commentary - Schabas, William, 1950-; Nowak, Manfred, 1950- (Kehl, Germany : N.P. Engel, 2019)
"The International Covenant on Civil and Political Rights is one of the components of the International Bill of Rights. This is an article-by-article commentary on the Covenant and its two Optional Protocols. For each provision, the preparatory work as well as the case law of the Human Rights Committee and the concluding observations on periodic reports by States Parties is reviewed. It is the third edition, substantially revising the second edition which was published in 2005"--
International Covenant on Civil and Political Rights -- First Optional Protocol to the International Covenant on Civil and Political Rights -- Second Optional Protocol to the International Covenant on Civil and Political Rights.
Includes bibliographical references and index.
Text of the articles in English and French; all other text in English.
Keywords: International Covenant on Civil and Political Rights -- (1966 December 16); International Covenant on Civil and Political Rights -- (1966 December 16). -- (1966 December 16); International Covenant on Civil and Political Rights -- (1966 December 16). -- (1989 December 15); International Covenant on Civil and Political Rights; Civil rights; Political rights; Civil rights; Political rights; Law commentaries; Law commentaries